Governing Climate Change - Bulkeley, Harriet, 1972-; Newell, Peter (Peter John) (New York : ROUTLEDGE, 2023)
This fully revised and expanded new edition provides a short and accessible introduction to how climate change is governed by an increasingly diverse range of actors, from civil society and business actors to multilateral development banks, donors, and cities. The issue of global climate change has risen to the top of the international political agenda. Despite ongoing contestation about the science informing policy, the economic costs of action and the allocation of responsibility for addressing the issue within and between nations, it is clear that climate change will continue to be one of the most pressing and challenging issues facing humanity for many years to come. The book: Evaluates the role of states and non-state actors in governing climate change at multiple levels of political organization: local, national, and global Provides a discussion of theoretical debates on climate change governance, moving beyond analytical approaches focused solely on nation-states and international negotiations Examines a range of key topical issues in the politics of climate change Includes multiple examples from both the north and the global south Providing an inter-disciplinary perspective drawing on geography, politics, international relations, and development studies, this book is essential reading for all those concerned not only with the climate governance but with the future of the environment in general.
includes index
OCLC-licensed vendor bibliographic record.
Keywords: Climatic changes -- Government policy -- International cooperation; POLITICAL SCIENCE / General; POLITICAL SCIENCE / History & Theory; POLITICAL SCIENCE / International Relations / General